PRODUCT QUALITY ANALYSIS IN INCREASING BUYING INTERESTIN THE TODAY'S FAST-FOOD BUSINESS - Muh. Husriadi; Bunga Kartika; Deprianus Sarlis (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Fast food industry​ current face challenges in maintaining interest buy consumers in the middle increasingly fierce competition strict especially regarding quality product that is a factor main decision purchase. This study aims to analyze in a way comprehensive in dimensions quality products in ready- to-eat food contemporary. The method used is qualitative research. descriptive with data collection through interview in-depth and observation participatory in consumers in Kendari City. The results of the study showed that the dimensions quality products that include authentic and consistent taste, attractive and functional packaging, relevant menu innovations, and consistency production have a role in improving interest buy. In addition, the attraction product, loyalty consumers, and recommendations from word of mouth participate strengthen the relationship. The implications of this research contribute theoretical in the development of marketing science culinary and practical for business actors in formulating strategies for increasing quality products for sustainable competitiveness.